Kualitas Layanan dan Harga terhadap Kepuasan Pelanggan: Studi Empiris pada Minuman dan Makanan - Adi Lukman Hakim; Erna Nur Faizah (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2023)
Quality service plays an important role in shaping customer satisfaction, but it is also closely related to creating profits for the company. The purpose of the study is whether service quality affects customer satisfaction, whether price affects customer satisfaction and whether service quality and price affect customer satisfaction. The analysis method used is descriptive analysis and multiple linear regression. This research was conducted in relation to the context (implementation of service quality, price and customer satisfaction). In addition, the theoretical gap (detailed perspective on each dimension) left by previous research. The results showed that service quality and price affect customer satisfaction at CafÃ© Gartenhutte Trawas. Quality and price show a multiple correlation 0.809 which shows a strong relationship between the independent variable and the dependent variable. This research has implications for businesses that should use their websites to convey information and offer the best customer service to increase perceived value.